2012
DOI: 10.1111/j.1476-5381.2011.01636.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin and bradykinin: ‘brothers‐in‐arms’ in Chagas vasculopathies?

Abstract: Reports of Chagas disease are increasing in non-endemic populations across the globe. Apart from vector eradication and prevention efforts by public health organizations, current pharmacological interventions are sparse and show important side effects. In this issue of the BJP, Andrade et al. elegantly demonstrate a new pharmacological paradigm whereby Trypanosoma cruzi host cell invasion requires significant cross-talk between receptors for kinins and endothelins. It is shown, for example, that acting via bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This mechanism can enhance parasite invasion of cardiovascular cells [188, 189]. TLR2, the B2 kinin and CXCR2 receptors trigger intracellular inflammatory pathways induced by T. cruzi and directly interact with endogenous ET-1 [188, 189].…”
Section: Chagas Disease and Endothelinmentioning
confidence: 99%
See 2 more Smart Citations
“…This mechanism can enhance parasite invasion of cardiovascular cells [188, 189]. TLR2, the B2 kinin and CXCR2 receptors trigger intracellular inflammatory pathways induced by T. cruzi and directly interact with endogenous ET-1 [188, 189].…”
Section: Chagas Disease and Endothelinmentioning
confidence: 99%
“…This mechanism can enhance parasite invasion of cardiovascular cells [188, 189]. TLR2, the B2 kinin and CXCR2 receptors trigger intracellular inflammatory pathways induced by T. cruzi and directly interact with endogenous ET-1 [188, 189]. Andrade et al demonstrated that HOE-140, a B2 kinin receptor (BK2R) antagonist can reduces the ET-1-induced increase in T. cruzi invasion seen in human smooth muscle cells in vitro [188, 189].…”
Section: Chagas Disease and Endothelinmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this evidence, D’Orléans-Juste and cols. (2012) raised the importance of investigations about the role of de novo induction of B 1 receptors by cytokines, in Chagas vasculopathies [ 149 ].…”
Section: Kinins and Their Implication In Protozoan And Parasite Inmentioning
confidence: 99%